2011
DOI: 10.1111/j.1365-3156.2011.02915.x
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of coupling Intermittent Preventive Treatment in infants with the Expanded Programme on Immunization in three francophone countries in Africa

Abstract: Abstractobjective Intermittent preventive treatment in infants (IPTi) is a malaria control strategy currently recommended by WHO for implementation at scale in Africa, consisting of administration of sulphadoxine-pyrimethamine (SP) coupled with routine immunizations offered to children under 1 year.In this study, we analysed IPTi acceptability by communities and health staff.methods Direct observation, in-depth interviews (IDIs) and focus group discussions (FGDs) were conducted in Benin, Madagascar and Senegal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Mothers' knowledge of immunization or other interventions is known to be positively correlated with full immunization rates [ 23 , 24 , 26 ] and it is possible that the adhesion of the community through information and sensitization was responsible for this increase in EPI vaccines coverage compared to baseline levels for all the vaccines and for the fact that this increase was more marked in the intervention zone compared to the non intervention zone. Acceptability surveys conducted in Mali (our unpublished data) and other countries in sub-saharan Africa [ 15 ] have found that mothers like IPTi and come more to health centers because i) they are concern with malaria; ii) they think it is an anti-pyretic (and post-vaccinal fever is one of the major bottlenecks of EPI coverage) and iii) it is free. Even in the context of maternal illiteracy, educating mothers about the vaccines and vaccine-preventable diseases was reported to be highly effective in increasing the immunization coverage [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mothers' knowledge of immunization or other interventions is known to be positively correlated with full immunization rates [ 23 , 24 , 26 ] and it is possible that the adhesion of the community through information and sensitization was responsible for this increase in EPI vaccines coverage compared to baseline levels for all the vaccines and for the fact that this increase was more marked in the intervention zone compared to the non intervention zone. Acceptability surveys conducted in Mali (our unpublished data) and other countries in sub-saharan Africa [ 15 ] have found that mothers like IPTi and come more to health centers because i) they are concern with malaria; ii) they think it is an anti-pyretic (and post-vaccinal fever is one of the major bottlenecks of EPI coverage) and iii) it is free. Even in the context of maternal illiteracy, educating mothers about the vaccines and vaccine-preventable diseases was reported to be highly effective in increasing the immunization coverage [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though the efficacy, the absence of interaction with EPI vaccines and safety of IPTi are well established, there are still concerns that addition of IPTi will result in an increase in the work burden and will disrupt the routines EPI services especially in Africa where the target EPI vaccines coverage remains to be met. However IPTi may also increase the adherence of the community to EPI services and improve EPI coverage, once the benefit of the strategy is perceived [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…This allows us to control for a father's ATR-adherence. If mother-specific factors rather than household-level factors drive our ATR estimate, we should find that ATR adherence of the mother has a larger effect on our outcome variables than ATR adherence of the father, because women in Benin have the primary responsibility when it comes to children's healthcare decisions (de Sousa et al, 2011;ONE, 2011b;Rashed et al, 1999).…”
Section: Subsample Analysis: Bed Net Owners and Father's Characteristicsmentioning
confidence: 98%
“…Aujoulat et al (2003), for instance, argue that cultural beliefs in southern Benin affect the demand for treatment of Buruli ulcer, a skin infection 12 which can lead to disfigurement and disability. Magico-religious beliefs in Benin are also said to affect malaria prevention and treatment (Rashed et al, 1999;de Sousa et al, 2011), and have been blamed for a low demand for vaccines, because some traditional healers have advised against their use (ONE, 2011a(ONE, , 2011bSoumonni, 2012). 16 Magico-religious beliefs do not always go against conventional medical prescriptions.…”
Section: Voodoo and Healthcare In Beninmentioning
confidence: 99%
See 1 more Smart Citation